The relationship between viso-motor skills and handwriting in students with dyslexia - Capellini, Simone Aparecida [UNESP]; Serrão, Flávia Santana [UNESP]; Del Bianco, Noemi; Germano, Giseli Donadon [UNESP]; Giaconi, Catia (My University, 2018)
Aim: To relate the viso-motor skills and handwriting of students with dyslexia. Methods: Twenty-two students with multidisciplinary diagnosis of dyslexia, aged from 8 years and 3 months to 13 years and 4 months, of both genders, from third to fifth grade of elementary school participated in this study. The students were submitted to the following procedures: Visual Perception Development Test III - DTVP III and Dysgraphia Scale. Results: The results indicated that most students with dyslexia were classified as dysgraphics. Therefore, from the analysis of the Visual Perception Development Test (DTVP-III) it was possible to observe that there was an impact of the variables related to the visomotor and fine motor skills. Conclusion: Nevertheless, the findings of this study indicate that dyslexic students presented difficulties in visomotor skills, thus impairing hand writing. Thus, most of these students presented compatible performance for disgraphic writing.
Keywords: Dyslexia; Handwriting; Viso-motor perception